2015
DOI: 10.1177/0014402915585477
|View full text |Cite
|
Sign up to set email alerts
|

Are Online Sources for Identifying Evidence-Based Practices Trustworthy? An Evaluation

Abstract: The use of evidence-based practices has become a focus in education since the No Child Left Behind Act of 2001 and the Individuals with Disabilities Education Act reauthorization of 2004 required using practices based on scientific research to improve student outcomes. Although many teachers may not have the time or expertise to evaluate the research base for these practices, the prevalence of Internet resources has increased their access to such information. However, web sites differ in type and quality of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Test, Kemp-Inman, Diegelmann, Hitt, and Bethune (2015) examined 47 educational websites that specifically claimed to provide evidence-based practices (EBPs) for students with and without disabilities. They categorized the websites into three groups: trust, trust with caution, and do not trust.…”
Section: Research On Website Usage and Qualitymentioning
confidence: 99%
“…Test, Kemp-Inman, Diegelmann, Hitt, and Bethune (2015) examined 47 educational websites that specifically claimed to provide evidence-based practices (EBPs) for students with and without disabilities. They categorized the websites into three groups: trust, trust with caution, and do not trust.…”
Section: Research On Website Usage and Qualitymentioning
confidence: 99%
“…The development and distribution of quality indicator checklists is one way researchers have promoted objective and uniform application of EBP quality indicators. One widely distributed checklist created by NSTTAC (Test et al, 2009) and NTACT (Test et al, 2015) …”
Section: Summary Of Overarching Findingsmentioning
confidence: 99%
“…As mentioned previously, the use of such practices may be detrimental to the people it serves. For example, an analysis of online resources used to identify EBPs found that only 57% of those resources were considered trustworthy (Test, Kemp-Inman, Diegelmann, Hitt, & Bethune, 2015). Professional and advocacy organizations such as TASH must be responsible for providing accurate and reliable information about the most effective and efficient teaching strategies.…”
Section: Relevance To Advocacy and Intervention Research For Persons mentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet gives students the opportunity to explore places without having to travel (e.g., virtual tours of apartments, businesses, museums). The Internet contains valuable, high-quality sources of information; however, it also contains unreliable, subjective sources of misinformation (Test, Kemp-Inman, Diegelmann, Hitt, & Bethune, 2015). The inconsistency with the web increases the burden placed on students and teachers to evaluate the quality of a website regardless of its intended use (Zhang & Duke, 2011).…”
Section: Step 1: Evaluate Web-based Resources To Explore Topics In Sementioning
confidence: 99%